History, Structure, Epidemiology and Molecular Typing of Staphylococcal Cassette Chromosomes Mec (Sccmec) involved in Multiple Resistances to Beta-Lactams in the Genus Staphylococcus: an Overview - Abasse, Ouédraogo Ganame; Boukare, Kabore; Hama, Cisse; Oumarou, Zongo; Henri, Ouedraogo Sidabewindin; Nestor, Bassole Imael Henri; Yves, Traore; Francois, Tchoumbougnang; Aly, Savadogo (Archives of Clinical and Biomedical Research, 2022)
Staphylococcal cassette chromosomes mec (SCCmec) are chromosomal mobile genetic determinants that confer to the Staphylococcus strain hosting a multi-resistance to antibiotics and metallic trace elements. The objective of this study was to review the literature on the history, structure, epidemiology and characterization techniques of SCCmec. Data were collected from articles in scientific journals through Google scholar and PubMed engines. In 1999, was characterized the first SCCmec type on genome of S. aureus N315. A type of SCCmec is characterized by the complex type ccr and the class complex mec. The first classification took place in 2001. Today, there are 15 recognized SCCmec types. SCCmec type IV is the most disseminated and predominates on the continents. The application of PCR and Illimina or MinION sequencing have revolutionized SCCmec typing, which is one of the main methods of epidemiological surveillance of methicillin resistance Staphylococcus aureus. MRSA are the most threatening bacteria in the hospital environment and cause enormous problems in community settings and in animal health. SCCmec typing is a very effective means of characterizing the genetic determinants of resistance in MRSA. Popularization of SCCmec typing through their applications in routines